2020
DOI: 10.1080/15548627.2019.1710430
|View full text |Cite
|
Sign up to set email alerts
|

DNA-dependent protein kinase regulates lysosomal AMP-dependent protein kinase activation and autophagy

Abstract: Macroautophagy/autophagy is a central component of the cytoprotective cellular stress response. To enlighten stress-induced autophagy signaling, we screened a human kinome siRNA library for regulators of autophagic flux in MCF7 human breast carcinoma cells and identified the catalytic subunit of DNAdependent protein kinase PRKDC/DNA-PKcs as a positive regulator of basal and DNA damage-induced autophagy. Analysis of autophagy-regulating signaling cascades placed PRKDC upstream of the AMPdependent protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…The treatment of M059K cells with DNA-PKcs antisense oligonucleotides caused radiation-induced autophagy and radiosensitized the cells. Similar observations were also obtained by Puustinen et al (2020) study. Inactivation or depression of DNA-PKcs increases ionizing radiation-induced cell autophagy as well as occurrence of cell apoptosis.…”
Section: Dna-pkcs In Autophagysupporting
confidence: 91%
“…The treatment of M059K cells with DNA-PKcs antisense oligonucleotides caused radiation-induced autophagy and radiosensitized the cells. Similar observations were also obtained by Puustinen et al (2020) study. Inactivation or depression of DNA-PKcs increases ionizing radiation-induced cell autophagy as well as occurrence of cell apoptosis.…”
Section: Dna-pkcs In Autophagysupporting
confidence: 91%
“…This finding suggests that DNA-PK is essential for activating AMPK under low energy levels as a result of glucose deprivation in mammalian cells. Similarly, another study confirmed that DNA-PKcs is a positive regulator of AMPK activity and was found to phosphorylate two residues on AMPKγ (S192 and T284) (Puustinen et al, 2020). Conversely, another study showed that an aging-related increase in DNA-PKcs activity led to decreased AMPK activity, via phosphorylation-mediated inhibition of Hsp90 chaperone activity toward AMPKαα2 (Park et al, 2017).…”
Section: Atm and Dna-pk Kinases Play A Key Role In Cellular Energy Sementioning
confidence: 90%
“… 117 , 118 , 119 The AMPK is itself regulated by phosphorylation, with the most notable regulators being Liver kinase B1 (LKB1) and ataxia-telangiectasia mutated (ATM). 120 , 121 , 122 , 123 , 124 , 125 LKB1 is often mutated in tumor cells, leading to dysregulation of energy sensing and autophagy regulation. In the nucleus ATM senses DNA damage and cytosolic ATM senses the levels of reactive oxygen species; ATM at both cellular locations phosphorylates and activates the AMPK.…”
Section: Autophagymentioning
confidence: 99%